AB0074 Daily exercise suppresses acute pro-inflammatory cytokine expression systemically and il-1Β locally in a murine model of gout. (12th June 2018) - Young, N.A.; Jablonski, K.; Sandoval, B.; Kalyanasundaram, A.; Harb, P.; Hampton, J.; Jarjour, W.; Schlesinger, N.
Abstract : Background: Recent gout clinical practice recommendations/guidelines released by the ACR (2012) and the ACP (2017) do not address exercise as an interventional strategy; in contrast, the 2016 EULAR gout recommendations suggest that regular physical activity might decrease the excess mortality associated with chronic hyperuricemia. Referencing animal studies performed nearly a half century ago, many rheumatologists recommend resting the involved joints during an acute attack. However, recent evidence has demonstrated the anti-inflammatory effects of exercise in patients with rheumatic disease. Objectives: The purpose of this study was to investigate the effects of exercise intensity on an immunological level in an animal model of gout by characterising pro-inflammatory cytokine expression. Methods: BALB/C-Tg(NFκB-RE-luc)-Xen mice were exercised daily by treadmill walking (45 min/day) at low intensity (35% VO2 max), moderate intensity (55% VO2 max), and high intensity (75% VO2 max). Following the 2 week training period, monosodium urate (MSU) crystal-mediated arthritis was induced by intra-articular injection of MSU crystals (0.5 mg) into the tibio-tarsal joint (ankle). At 16 hours post-MSU crystal injection, tissue was collected for immunohistochemistry (IHC) and both serum and synovial aspirates were processed to measure cytokine levels. Results: Infiltrates consisted primarily of neutrophils and macrophages, as determined by IHC. The inflammatory responses were significantly reduced with low and moderate exercise when compared to either high intensity training or mice that were not exercised. Electrochemiluminescence detection assays quantifying the expression of a panel of pro-inflammatory cytokines showed that IL-2, IL-4, IL-5, IL-10, and IFN-γ were not detectable in the serum of MSU crystal-injected mice at levels greater than un-injected male/female controls. Furthermore, IL-12, CXCL1, TNF-α, and IL-6 expression was elevated in the serum with MSU crystal injection compared to un-injected counterparts, but this response was suppressed with low, moderate, or high intensity exercise training and undetectable in synovial aspirates. Conversely, IL-1β was not induced relative to un-injected controls systemically in the serum, but was increased locally in synovial aspirates. IHC staining of the ankle joint region for IL-1β confirmed this observation and further demonstrated a significant inhibition with low and moderate exercise relative to both high intensity training and non-exercised controls. Conclusions: Our results demonstrate that daily exercise can have a measurable effect systemically in reducing pro-inflammatory cytokine expression in MSU crystal-mediated arthritis. Moreover, high-intensity exercise can suppress pro-inflammatory cytokine expression systemically, however, only low/moderate training suppressed the localised inflammatory response. Collectively, these data suggest a paradigm shift; emphasising physical activity in gout patients is potentially efficacious and warrants further investigation. References: [1] Khanna D, et al. Arthritis Care Res2012;64:1447. [2] Richette P, et al. Ann Rheum Dis2017;76:29. [3] Dorwart BB, et al. Arthritis Rheum1974;17:563. Acknowledgements: Support provided by Ironwood Pharmaceuticals, Cambridge MA 02142 Disclosure of Interest: None declared